Why does "green" matter in supply chain management? Exploring institutional pressures, green practices, green innovation, and economic performance in the Chinese chemical sector - Wen, Xu; Cheah, Jun-Hwa; Lim, Xin-Jean; Ramachandran, Sridar (Elsevier, 2023)
There is a growing concern over the depletion of natural resources caused by rapid industrialization and its impact on the environment. As a response to these concerns, many companies are now focusing on implementing green supply chain management (GSCM) practices and green innovation (GI) as part of their environmental strategies to improve their economic performance (EP). Empirical evidence regarding the actual effects of these practices on the economic performance of Chinese chemical companies is still limited, warranting further investigation. To close the gap, this study utilizes the resource-based view and Institutional Theory to explore how three types of institutional pressures influence GSCM practices in Chinese chemical companies. Additionally, it examines the role of top management support (TMS) in shaping the relationship between GSCM practices and economic performance. The PLS-SEM approach was used to analyze the data gathered from 414 samples from listed Chinese chemical companies. The findings of the study revealed four key outcomes: First, institutional pressures have a positive influence on the adoption of GSCM practices by companies. Second, both GSCM practices and GI have a positive impact on economic performance, indicating that companies can enhance their economic performance by incorporating environmentally friendly practices. Third, GI acts as a mediator between GSCM practices and economic performance, indicating that the implementation of GI plays a crucial role in improving companies' economic outcomes through GSCM practices. Lastly, the relationship between GSCM practices and economic performance is strengthened when top management provides strong support for these initiatives. Overall, these findings not only have an academic impact on the supply chain domain but also provide effective environmental management practices to the top managers in Chinese chemical sector, allowing them to make decisions that benefit organizational efficiency, innovation, and performance. By identifying the factors that drive the adoption of GSCM practices and their influence on economic performance, the study offers valuable guidance for companies to integrate sustainable practices into their operations.